Vloga sonikacije v diagnostiki okužb umetnih vsadkov - Kocjančič, Boštjan (Zdravniški vestnik, 2014)
Prosthetic joint infection represent a devastating complication after joint arthroplasty and causes severe patient morbidity, along with the financial burden for the healthcare system. The number of patients after joint arthtroplasty increases with the ageing population, therefore there is an increase in the incidence of complications. The pathogenesis of medical device infection is based on the developement of bacterial biofilm, a diagnostic and therapeutic obstacle. The implementation of a new diagnostic tool % sonication, enables disruption of bacterial biofilm and improves the sensitivity of microbiological tests, even after preoperative antimicrobial therapy. In the period from February 2008 to December 2012 we studied 198 cases of revision surgery in the Department of Orthopaedic surgery in UKC Ljubljana, in wich an infection was suspected. We studied the use of sonication of explanted orthopedic material as an add-on diagnostic tool and compared it to standard soft tissue biopsy cultures. In 14 (7,1 %) cases infection was proven only by soft tissue biopsies (negative sonication), 62 cases (31,3 %) were diagnosed by both methods, additional 51 cases (25,7 %) were diagnosed only by sonication of explanted material and in 71 cases (35,9 %) all results were negative. Our results show that sonication is a superior tool (p < 0,05) for the detection of pathogens compared to soft tissue biopsy and could improve the treatment of orthopedic implant infections. Method can be used in all fields of orthopedic surgery thou it is most commonly used in the field of periprothetic revisions. Sonication is an excellent addition to standard diagnostic methods. The use of sonication is indicated in doubt- ful cases, where the distinction between aseptic failure and prosthetic joint infection is blurred.
Keywords: biofilm; diagnostika; joint prosthesis; proteze; sklepne proteze; sonication; sonikacija; vnetja